2017
DOI: 10.3389/fcimb.2017.00045
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance in Acinetobacter baumannii MDR-ZJ06 Revealed by a Multiomics Approach

Abstract: Acinetobacter baumannii has emerged as an important opportunistic pathogen due to its ability to acquire resistance to most currently available antibiotics. Colistin is often considered as the last line of therapy for infections caused by multidrug-resistant A. baumannii (MDRAB). However, colistin-resistant A. baumannii strain has recently been reported. To explore how multiple drug-resistant A. baumannii responded to colistin resistance, we compared the genomic, transcriptional and proteomic profile of A. bau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
(33 reference statements)
1
34
0
Order By: Relevance
“…Our findings demonstrated colistin and polymyxin B made mcr-1 -mediated resistant bacteria to exhibit different proteome profiles and it suggest that colistin-resistant bacteria might alter their metabolism to adapt to antibiotic resistance (Fig 1D). Proteomic characteristics discovered by SWATH-MS showed that mcr-1 could cause the disturbed metabolic regulation such as glycerophospholipid metabolism, thiamine metabolism, LPS biosynthesis, and CAMP resistance (Fig 3) and the protein profile of E. coli carrying mcr-1 to colistin showed the most significant changes, which was consistent with the report of Hua et al [24]. Integrative proteomic and metabolomic analysis demonstrated that GlpQ, EutE involved in glycerphospholipid metabolism were significantly up-regulated in colistin-resistant E. coli DH5α (pUC19- mcr-1 ) under the condition of blank LB broth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings demonstrated colistin and polymyxin B made mcr-1 -mediated resistant bacteria to exhibit different proteome profiles and it suggest that colistin-resistant bacteria might alter their metabolism to adapt to antibiotic resistance (Fig 1D). Proteomic characteristics discovered by SWATH-MS showed that mcr-1 could cause the disturbed metabolic regulation such as glycerophospholipid metabolism, thiamine metabolism, LPS biosynthesis, and CAMP resistance (Fig 3) and the protein profile of E. coli carrying mcr-1 to colistin showed the most significant changes, which was consistent with the report of Hua et al [24]. Integrative proteomic and metabolomic analysis demonstrated that GlpQ, EutE involved in glycerphospholipid metabolism were significantly up-regulated in colistin-resistant E. coli DH5α (pUC19- mcr-1 ) under the condition of blank LB broth.…”
Section: Discussionsupporting
confidence: 90%
“…It was noteworthy that the fatty acyl side chains with the C 12 -C 14 carbon chain of the lipid A group, which was essential for the maintenance of bacterial LPS function, were involved in the synthesis of bacterial fatty acid type II synthesis pathway, suggesting that it was essential to decipher the metabolic mechanism of mcr-1 mediated resistance from a metabolic perspective. Hua et al [24] utilized a multiomics approach to explore the response of multiple drug-resistant A. baumannii to colistin and found that RND efflux pump system were over-expressed and inhibited the expression of FabZ and β-lactamase. However, as a lipid-modified gene, the comprehensive proteomic and metabolomic profiling of mcr-1 -mediated colistin resistance in bacteria is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing (WGS) by Hiseq (Illumina, Carlsbad, CA) were performed as described previously. 8 Bacteria from a single colony were cultured overnight at 37°C in MH broth. The genomic DNA was extracted via a QIAamp DNA minikit (Qiagen, Valencia, CA, USA) following the protocol of the manufacturer's protocol.…”
Section: Whole Genome Sequencing and Analysismentioning
confidence: 99%
“…2 Although both tigecycline and colistin have been used effectively in the treatment of A. baumannii previously, resistant isolates have been reported. 7,8 While traditionally associated with nosocomial infections, A. baumannii is more frequently attributed to community-acquired pneumonia (CAP) in tropical and sub-tropical climates. 4,9,10 Although CAP strains are typically more susceptible to antibiotics than strains implicated in hospital acquired infections (HAI), CAP caused by A. baumanni is characterized by a fulminant and severe infection with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to colistin is considered as the most significant factor for emerging of colistin resistance (2), however, details of the in vivo response of A. baumannii to colistin exposure, such as the number of days for development of resistance was not described. The molecular studies about colistin resistance indicated two main mechanisms: modifications in lipid A structure and complete loss of LPS (3). By this study, we analyzed adaptation of A. baumannii to colistin use on a disease course of a patient.…”
mentioning
confidence: 99%